2008
DOI: 10.3382/ps.2007-00337
|View full text |Cite
|
Sign up to set email alerts
|

Guar Meal Diets as an Alternative Approach to Inducing Molt and Improving Salmonella Enteritidis Resistance in Late-Phase Laying Hens

Abstract: Induced molting of laying hens is a practice used by commercial egg producers to increase the productive lifetime of their flock. However, the conventional method of inducing molt, which involves removal of feed, water, or both as well as a reduction in photoperiod to less than a natural day has drawn criticism due to animal welfare and food safety concerns. The objective of this study was to explore the efficacy of diets containing high levels of guar meal (GM) in inducing molt and reducing susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…It has been reported that laying hens induced to molt by GM feeding exhibit improved resistance to Salmonella Enteritidis colonization when compared with hens molted by complete feed withdrawal. Furthermore, supplementation of β-mannanase (Hemicell) to diets containing high levels of GM appears to enhance resistance to Salmonella Enteritidis colonization in molted laying hens (Gutierrez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that laying hens induced to molt by GM feeding exhibit improved resistance to Salmonella Enteritidis colonization when compared with hens molted by complete feed withdrawal. Furthermore, supplementation of β-mannanase (Hemicell) to diets containing high levels of GM appears to enhance resistance to Salmonella Enteritidis colonization in molted laying hens (Gutierrez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of β-Mannanase in poultry diets containing guar meal has revealed beneficial impacts like lowered viscosity of intestinal digesta, better growth performance, improved FCR (Lee et al, 2003b; Ehsan, and Torki, 2010) optimum gut health and immune status (Mehri et al, 2010). Moreover, it enables the bird to fight Salmonella enteritis (Gutierrez et al, 2008). β-mannanase hydrolyzes β-1, 4-glycosidic bonds in β-mannans (Ooi and Kikuchi, 1995).…”
Section: Methods To Improve the Nutritive Value Of Guar Mealmentioning
confidence: 99%
“…Fernandez [112] demonstrated that feeding of chickens with yeast-derived MOS or palm kernel meal decreased S. enteritidis numbers, while increasing the numbers of probiotic lactic acid bacteria. By feeding laying hens guar meal supplemented with ␤-mannanase, Gutierrez et al [111] could demonstrate the combined positive effects of natural molting (the non-starch polysaccharides in guar meal cannot be used as energy source) with improved resistance to S. enteritidis.…”
Section: Animal Feedsmentioning
confidence: 98%
“…To stimulate multiple egg laying cycles and improve egg quality, laying hens are often starved for food or water (called molting), which are detrimental to their health and making them often more susceptible to Salmonella enteritidis infections [111]. Fernandez [112] demonstrated that feeding of chickens with yeast-derived MOS or palm kernel meal decreased S. enteritidis numbers, while increasing the numbers of probiotic lactic acid bacteria.…”
Section: Animal Feedsmentioning
confidence: 99%